Effect of oxygen content on magnetization and magnetoresistance properties of CMR manganites - Trukhanov, S. V.; Troyanchuk, I. O.; Korshunov, F. P.; Sirenko, V. A.; Szymczak, H.; Baerner, K. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2001)
The influence of oxygen content on the magnetization and electrical resistivity of Ln0.5A0.5MnO3 (Ln=La,Pr,Nd; A=Ca,Ba) manganites with the perovskite structure is investigated. It is shown thatthe La0.5Ca0.5MnO3-g compound undergoes a sequence of transitions from an antiferromagnetic (g=0) toa spin-glass (g=0.17) state and then to an inhomogeneous ferromagnetic (g=0.3) state. A transition from an antiferromagnetic charge-ordered state to a ferromagnetic charge-disordered state in Nd0.5Ca0.5 MnO3-gis observed as the oxygen content is reduced to where g=0.07. The Nd0.5Ba0.5 MnO3-g compound shows an increase of the Curie point from 110 K (g=0) up to 310 K (g=0.3). In addition, a largemagnetoresistance is revealed which develops below their Curie temperature despite the absence ofMn3+√Mn4+ pairs. A Zener double-exchange interaction is usually used in literature to explain themagnetic and electrical properties of hole-doped perovskite manganites. The data obtained support the mechanism of superexchange interactions between magnetic moments of the manganese ions via oxygen.